Innovations and Improvements in Pharmacokinetic Models Based on Physiology - Andrea Abbiati, Roberto; Manca, Davide (Current Drug Delivery, 2017)
Background: Accompanied by significant improvements of modeling techniques and computational methods in medical sciences, the last thirty years saw the flourishing of pharmacokinetic models for applications in the pharmacometric field. In particular, physiologically based pharmacokinetic (PBPK) models, grounded on a mechanistic foundation, have been applied to explore a multiplicity of aspects with possible applications in patient care and new drugs development, as in the case of siRNA therapies. Method: This article summarizes the features we recently introduced in PBPK modeling within a threeyear research project funded by Italian Research Ministry. Four major points are detailed: (i) the mathematical formulation of the model, which allows modulating its complexity as a function of the administration route and active principle; (ii) a dedicated parameter of the PBPK model quantifies the drugprotein binding, which affects the active principle distribution; (iii) the gall bladder compartment and the bile enterohepatic circulation process; (iv) the coupling of the pharmacokinetic and pharmacodynamic models to produce an overall understanding of the drug effects on mammalian body. Results: The proposed model is applied to two separate endovenous (remifentanil) and oral (sorafenib) drug administrations. The resulting PBPK simulations are consistent with the literature experimental data. Blood concentration predictability is confirmed in multiple reference subjects. Furthermore, in case of sorafenib administration in mice, it is possible to evaluate the drug concentration in the liver and reproduce the effects of the enterohepatic circulation. Finally, a preliminary application of the coupling of the pharmacokinetic/pharmacodynamic models is presented and discussed.
Keywords: Enterohepatic circulation